2014
DOI: 10.2304/plat.2014.13.3.232
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Change in Psychology Students' Acceptance of the Scientific Foundation of the Discipline

Abstract: Two studies explored conceptual change in undergraduate psychology students' acceptance of the scientific foundations of the discipline. In Study 1, Introductory Psychology students completed the Psychology as Science questionnaire (PAS) at the beginning and end of the semester and did so from their own (Self Condition) and their instructors' (Professor Condition) perspectives. Study 2 replicated Study 1 with advanced students enrolled in research-oriented courses. In both studies, students had higher PAS scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Based on three factor scores of the PAS, namely reflecting students' beliefs about psychology as a science, their appreciation of psychological research, and their views about predictability of behavior, we found that students in the northeast (Morales et al, 2005) and the south (Bartoszeck et al, 2005) of Brazil were ambivalent toward the status of psychology as a science and that this is due in part to the lack of published research and the maintaining of psychology research laboratories throughout Brazil. These conclusions are consistent with recent research conducted with American samples, which found that students' beliefs associated with psychology as a science were positively associated with professors' appreciation of psychology as a science (Amsel, Ashley, Baird, & Johnston, 2014;Amsel et al, 2009) and with participation in courses that emphasize research methodology and/or require students to complete a research project (Amsel et al, 2011;Friedrich, 1996;Holmes & Beins, 2009;Pettijohn et al, 2015).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Based on three factor scores of the PAS, namely reflecting students' beliefs about psychology as a science, their appreciation of psychological research, and their views about predictability of behavior, we found that students in the northeast (Morales et al, 2005) and the south (Bartoszeck et al, 2005) of Brazil were ambivalent toward the status of psychology as a science and that this is due in part to the lack of published research and the maintaining of psychology research laboratories throughout Brazil. These conclusions are consistent with recent research conducted with American samples, which found that students' beliefs associated with psychology as a science were positively associated with professors' appreciation of psychology as a science (Amsel, Ashley, Baird, & Johnston, 2014;Amsel et al, 2009) and with participation in courses that emphasize research methodology and/or require students to complete a research project (Amsel et al, 2011;Friedrich, 1996;Holmes & Beins, 2009;Pettijohn et al, 2015).…”
supporting
confidence: 88%
“…It is possible that students model their professors' lack of appreciation for natural scientific paradigm, low motivation to do research, and their theoretical cognitive style characterized by high level of abstraction associated with a preference for conceptual analysis of psychological phenomena over scientific examination of reality (Allakhverdov, 2005;Bodalev & Stolin, 1988;Dvoinin, 2015;Mironov, 2004). It is not surprising that Russian psychology professors and advisers holding such beliefs (Amsel et al, 2014) and having low involvement in research (Morales et al, 2005) do not see any value in students' research activities #9&…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More attention might also be devoted to discussing degree and field beliefs and stereotypes with both lower- and upper-division psychology majors and minors. Researchers (e.g., Amsel, Ashley, Baird, & Johnston, 2014) have shown that students' knowledge of psychology as a science can be positively influenced by their psychology professors. Accordingly, professors' views about and their efforts to address, clarify, or counter psychology misconceptions are likely to have a positive effect on student knowledge and beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Linderberg’s philosophy of teaching echoes the discussion of complexity of teaching in recognizing that there is an “unending list of characteristics of an excellent teacher.” But she focuses on key features which work for her students. Her goal is “to teach the students the scientific nature of psychology and hopefully show them how psychology is ubiquitous.” A focus on foundational issues of the science of the discipline and its application is notable, given the stereotypes held about the discipline and challenges in overcoming them (Amsel, Ashley, Baird, & Johnston, 2014; Brinthaupt, Hurst, & Johnson, 2016; Pettijohn et al, 2015). It also represents an important pedagogical and curricular movement away from the personal and more toward the scientific within the teaching of high school psychology (Keith, Hammer, Blair-Broeker, & Ernst, 2013)…”
Section: Mary Margaret Moffett Memorial Teaching Excellence Awardmentioning
confidence: 99%